Valuation of commodity option prices under a regime-switching model with stochastic convenience yield: Model calibration using flower pollination optimization algorithm - Hamdi, A.; Aksikas, I.; Smaoui, H.; Mehrdoust, F.; Noorani, I. (Journal of computational and applied mathematics, 2026)
This research work seeks to construct a model for commodity spot prices by incorporating the concept of stochastic convenience yield within a Markov-switching framework. The model presented in this paper applies the Gibson-Schwartz commodity model under the risk-neutral measure, enabling regime-switching in the convenience yield and spot price dynamics. Using the WTI crude oil spot prices, the parameters involved in the proposed commodity regime-switching model are estimated by expectation–maximization algorithm. We then carry out a semi-analytical formula for the commodity futures contracts and European option price written on them. We calibrate the option pricing model parameters using the flower pollination optimization algorithm based on the European call option prices in WTI crude oil market. The results show that the provided Markov-switching model, whose parameters are calibrated by the flower pollination optimization algorithm is superior to the some common models in commodity literature.